ChemInform Abstract: "One‐Pot" Access to Dihydrofurans via Tandem Oxidative Difunctionalization and Ring Contraction of Aminopyrans. Issue 48 (2nd December 2014) - Mandha, Santhosh Reddy; Alla, Manjula; Nanubolu, Jagadeesh Babu
Abstract The sequential addition of NCS and a base to 2‐amino‐4H‐pyran derivatives (I) and (IV) in alcohol medium affords dihydrofurans (III) and (V), resp., in good yields.